A política externa de Angola e as estratégias atuais - Jovita, João Baptista de (2017)
This dissertation aims to study the current strategies of Angolan foreign policy, considering the 41 years since its independence. The study presents two models to analyze two forms of Angolan international insertion. The first model applies to the period from 1975 to 1991, which emphasizes the agenda of defense, peace and security that implied Angola to seek for a isolated international insertion, face of the Cold and Civil Wars. Already the second model applies to the period from 1992 to 2016, which analyzes how Angola sought to adapt to the new international context in the post-Cold and Civil Wars. The research questions how Angola formulated its strategic interests throughout these periods and what are its reflexes for current strategies. Most of the earlier studies characterize Angola only as the "recipient" of the major powers' foreign policies. This study complies with this historical premise, but argues that the relations built with the great powers have formed a fundamental factor in proposing the country's own regional dynamics, transforming, over time, Angola in as a prominent actor in international relations, both at the regional and global levels.